2002
DOI: 10.1242/jcs.00165
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-2 expression induces cation-selective channels in tight junctions of epithelial cells

Abstract: Tight junctions seal the paracellular pathway of epithelia but, in leaky tissues, also exhibit specific permeability. In order to characterize the contribution of claudin-2 to barrier and permeability properties of the tight junction in detail, we studied two strains of Madin-Darby canine kidney cells(MDCK-C7 and MDCK-C11) with different tight junctional permeabilities. Monolayers of C7 cells exhibited a high transepithelial resistance (>1 kΩ cm2), compared with C11 cells (<100 Ωcm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
644
4
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 735 publications
(686 citation statements)
references
References 35 publications
35
644
4
3
Order By: Relevance
“…However, our cingulin-depleted clones were obtained from MDCKII cells, which already express claudin-2, and have a relatively low TER. Cingulin-depleted monolayers showed a slight decrease in TER values at 4 -8 h after start of junction assembly by the calcium switch, consistent with the notion that increased claudin-2 levels correlate with lower TER, due to increased permeability to cations (Amasheh et al, 2002). However, this decrease in TER was not statistically significant, and at steady-state the barrier function of cingulin-depleted clones was similar to WT cells.…”
Section: Discussionsupporting
confidence: 73%
“…However, our cingulin-depleted clones were obtained from MDCKII cells, which already express claudin-2, and have a relatively low TER. Cingulin-depleted monolayers showed a slight decrease in TER values at 4 -8 h after start of junction assembly by the calcium switch, consistent with the notion that increased claudin-2 levels correlate with lower TER, due to increased permeability to cations (Amasheh et al, 2002). However, this decrease in TER was not statistically significant, and at steady-state the barrier function of cingulin-depleted clones was similar to WT cells.…”
Section: Discussionsupporting
confidence: 73%
“…), indicating that charge preference was not affected by TRIC-a ( Figure 5B). Especially for the TRa-4 clone this underlines that the change in claudin-2 expression had no functional relevance, because a change in Na ϩ permeability would be expected after elevated expression of properly located claudin-2, because claudin-2 is known to form specific paracellular channels for small cations Amasheh et al, 2002).…”
Section: Tricellulin-induced Barrier Exhibits No Charge Preference Anmentioning
confidence: 99%
“…Single-ion permeabilities were determined from dilution or bi-ionic potentials and the Goldman-Hodgkin-Katz equation as reported previously (Amasheh et al, 2002;Gü nzel et al, 2009;Yu et al;. Briefly, NaCl dilution potentials were measured by switching one hemichamber to a solution containing a reduced concentration of NaCl and all other components identical to standard Ringer's.…”
Section: Electrophysiologymentioning
confidence: 99%
“…Another gene included in this category is claudin, a component of tight junction filaments capable of interacting adhesively with complementary molecules on adjacent epithelial cells (Gonzalez-Mariscal et al, 2003). Recent studies have found that over-expression of claudin-2 induces cation-selective channels in tight junctions of epithelial cells resulting in increased ion permeability (Amasheh et al, 2002). Other genes include supervillin, an F-actin bundling plasma membrane protein that contains functional nuclear localization signals (Wulfkuhle et al, 1999), bamacan, a chondroitin sulphate proteoglycan that abounds in basement membranes and is thought to be involved in the control of cell growth and transformation (Ghiselli et al, 1999) and osteonectin which has previously been demonstrated to be increased in human age-related cataracts (Kantorow et al, 2000).…”
Section: Gene Expression Profiles Of Human Age-related Cataractsmentioning
confidence: 99%